Implementation Of Multimedia Call Centre With Computer Telephony Integration - Tan, Kok Eng (2003)
The objective of this project is to use Avaya Multimedia Contact Centre Platform to implement seamless integration between the communication channels and client/agent desktop's application. The concept of Customer Relationship Management (CRM) is used to provide interaction management and business intelligent solution to customer as well as service provider.